Analysis of the Factors Influencing Consumer Purchase Interest in Printing and Screen Printing Businesses at Sepakatea Advertising Broni Jambi City - Anita Nur Hijannah; Arsa; Sri rahma (PT FORMOSA CENDEKIA GLOBAL, 2023)
Price, Product Quality and Service Quality are several factors that influence consumer buying interest. Quality products and services at affordable prices will attract consumers to buy. The purpose of this study was to determine the effect of price, product quality and service quality on consumer buying interest at Sepakatea Adertising Broni, Jambi City. The method used is a quantitative research method. The number of samples in this study were 81 people. Multiple Regression Analysis is used as a data analysis technique. The results showed that the Price Variable had a positive but not significant effect on consumer buying interest, the Product Quality Variable had a positive and significant effect on Consumer Buying Interests and the Service Quality Variable had no significant effect on purchasing decisions. Based on data analysis in this study, these variables are valid and reliable.